Assessing the reproducibility of high definition urethral pressure profilometry and its correlation with an air‐charged system. Issue 5 (30th August 2016) - Klünder, Mario; Amend, Bastian; Sawodny, Oliver; Stenzl, Arnulf; Ederer, Michael; Kelp, Alexandra; Sievert, Karl‐Dietrich; Feuer, Ronny
Abstract : Introduction: Recently, a new urodynamic method for the assessment of stress urinary incontinence called high definition urethral pressure profilometry (HD‐UPP) has been introduced. This method combines a novel microtip catheter with advanced signal processing to enable spatial data location and the reconstruction of a pressure image inside the urethra. In order to assess the reproducibility of HD‐UPP data, we statistically evaluate HD‐UPP datasets and compare them to data from a double balloon air‐charged system. Materials and Methods: Both catheters are used on sedated female minipigs. Data from the microtip catheter are processed through a signal reconstruction algorithm, urodynamic features are extracted, and compared to the air‐charged system. Reproducibility of HD‐UPP data is assessed by statistically evaluating consecutive, intra‐individual datasets. Results: HD‐UPP delivers results in agreement with previous comparisons of microtip and air‐charged systems. The average deviation of two consecutive, intra‐individual pressure images is very low at 7 cm H2 O. Conclusions: HD‐UPP provides physicians with detailed information on the pressure distribution inside the urethra. Through comparison with an air‐charged catheter, it is shown that HD‐UPP delivers results in agreement with previous studies on the comparison of microtip and air‐charged catheters. It provides excellent reproducibility, as the difference between sequentially measured profiles from the same minipig is significantly lower than the one between profiles from different minipigs.